Technological potential of Kazakhstan: assessment and development opportunities - G. Kh. Umarova; A. T. Mergenbaeva; G. G. Shinet (Экономика: стратегия и практика, 2020)
The successful development of national economies requires a certain technological potential. Technological advantages have become a decisive factor in international competition, so it is extremely important to achieve the implementation of the accumulated technological potential and its further strengthening. The article assesses the current state of the technological potential of Kazakhstan An analysis of existing domestic and foreign approaches to the assessment of technological potential. The current state of scientific and technical potential of Kazakhstan is assessed. It was noted that in recent years the country has taken measures to create new forms of science funding management, but the level of scientific and technological potential still does not fully meet the needs of society, the needs of the real sector of the economy. The subject of the research is the technological potential of the development of innovative economy in Kazakhstan to ensure the country’s global competitiveness in the world market.